The Implementation of Jigsaw Technique with Musical Background in Comprehending Reading Text - Ammang Latifa; Rafi’ah Nur; Muhammad Faried Wadjedy (Celt: A Journal of Culture, English Language Teaching & Literature, 2020)
This research studies the impact of the implementation of the Jigsaw technique with a musical background to comprehend reading at Senior high school in Sidrap, Indonesia. This research uses a quasi-experimental method to answer the question, "is the use of Jigsaw with a musical background as a technique able to improve the reading comprehension of senior high students at senior high school? This research also uses a random sampling technique to select the sample in the experimental and control class.  The data is analyzed by using descriptive statistics. The result of the calculation of students' scores from the post-test indicates that there is a significant improvement in students' comprehension achievement before and after learning reading by using the Jigsaw technique with background music. The result of this research finally shows that the use of the Jigsaw technique with background music improves the reading comprehension of the eleventh-grade students of senior high school in Sidrap, Indonesia. It is proved by the students' comprehension in the reading text that was 42.3 in their pre-test, but increasing in the post-test by mean score was 63.35. It means that the alternative hypothesis is accepted, which the t-test value is more significant than the t-table value. In the post-test, the t-test value is 11.92, while the t-table value is 2.042. Based on the result of data analysis, the writer concludes that using the Jigsaw technique with background music is useful to improve the reading comprehension of the student in reading text.